Strategic capacity choice under uncertainty: the impact of market structure on investment and welfare - Veronika Grimm; Gregor Zoettl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2008)
We analyze a market game where firms choose capacities under uncertainty about future market conditions and make output choices after uncertainty has unraveled. We show existence and uniqueness of equilibrium under imperfect competition and establish that capacity choices by strategic firms are generally too low from a welfare point of view. We also demonstrate that strategic firms choose even lower capacities if they anticipate competitive spot market pricing (e.g. due to regulatory intervention). We finally illustrate how the model can be used to assess the impact of electricity market liberalization on total capacity and welfare by fitting it to the data of the German electricity market.
Keywords: D43; L13; D41; D42; D81; 330; Investment incentives; demand uncertainty; cost uncertainty; Cournot competition; First Best; Second Best; capacity obligations; spot market regulation; Elektrizitätswirtschaft; Kapazitätsplanung; Entscheidung bei Unsicherheit; Marktstruktur; Spieltheorie; Spotmarkt; Regulierung; Investition; Ökonomischer Anreiz; Theorie